2020
DOI: 10.1101/2020.06.18.160317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wolbachiaand virus alter the host transcriptome at the interface of nucleotide metabolism pathways

Abstract: Wolbachia is a maternally transmitted bacterium that manipulates arthropod and nematode 28 biology in myriad ways. The Wolbachia strain colonizing Drosophila melanogaster creates sperm-29 egg incompatibilities and protects its host against RNA viruses, making it a promising tool for 30 vector control. Despite successful trials using Wolbachia-transfected mosquitoes for Dengue 31 control, knowledge of how Wolbachia and viruses jointly affect insect biology remains limited.32 Using the Drosophila model, transcri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 72 publications
4
14
0
Order By: Relevance
“…Due to the cytological defects imposed by Wolbachia on host chromosomes, it has been long thought that Wolbachia may modify host epigenomes (Harris and Braig, 2003;Negri et al, 2009;Zhang et al, 2013). Recent work on the T. pretiosum and D. melanogaster transcriptome and epigenome showed altered splicing of various host genes in response to Wolbachia (Wu et al, 2020;Lindsey et al, 2020).…”
Section: Parthenogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the cytological defects imposed by Wolbachia on host chromosomes, it has been long thought that Wolbachia may modify host epigenomes (Harris and Braig, 2003;Negri et al, 2009;Zhang et al, 2013). Recent work on the T. pretiosum and D. melanogaster transcriptome and epigenome showed altered splicing of various host genes in response to Wolbachia (Wu et al, 2020;Lindsey et al, 2020).…”
Section: Parthenogenesismentioning
confidence: 99%
“…In Drosophila, however, expression of Dnmt2 is induced in the presence of Wolbachia and provides antiviral defense (Durdevic et al, 2013;Bhattacharya et al, 2017;. A comprehensive RNAseq analysis revealed a tripartite interplay between Wolbachia, virus, and host at the interface of nucleotide metabolism, with Wolbachia and virus downregulating the pyrimidine and purine synthesis pathways, respectively (Lindsey et al, 2020). In particular, the prat2 gene involved in de novo synthesis of purine nucleotides (Ji and Clark, 2006) was upregulated in Wolbachia-infected flies; and knockdown of prat2 mRNA levels showed a Wolbachia-dependent impact on viral replication, with knockdown being pro-viral in the presence of Wolbachia and antiviral in the absence of Wolbachia (Lindsey et al, 2020).…”
Section: Pathogen Resistancementioning
confidence: 99%
“…In particular for cholesterol, providing or restoring its intracellular traffic recover virus replication in a Wolbachia-infected host, indicating both the role of cholesterol in virus development and Wolbachia interference in host lipid availability (55,56). In another recent example, it was found that Wolbachia and virus have antagonistic effect in the host expression of prat2, a gene involved in nucleotide synthesis (57).…”
Section: The Possible Mechanismsmentioning
confidence: 99%
“…Very few studies have studied Wolbachia physiology, and metabolomic approaches will likely be fruitful in understanding the interplay between Wolbachia and host. Additionally, dual RNA-seq of host and Wolbachia transcriptomes, either alone or coupled to metabolomics, is also likely to be a fruitful direction for understanding the symbiosis [172].…”
Section: Future Directionsmentioning
confidence: 99%